Development of wireless based potentiostat in biomedical applications - Janyasupab, Metini; Asavakijthananont, Narawee (My University, 2019)
Wirelessly integrated and portable electronics designs of analytical systems are of great importance to support future technological platforms including internet of things (IoT), artificial intelligence (AI), precision medicine, and wearable chemical/biological sensing systems. In this study, a simple and robust prototype of the so-called potentiostat, electrochemical instrumental system, with a wireless data acquisition and user control is demonstrated. With a wide range of potential applications, the developed system can be conveniently customizable to detect chemical of interest in food safety, continuous at-home diagnosis, environmental monitoring, and low-power energy storage. The device is comprised of two major units: a modified front-end sensor (Texas Instrument, LMP91000EVM), and a development board (Espressif, ESP32) implementing with a programmable saw tooth waveform to assess cyclic voltammetry (CV), the most common electrochemical measurement with the three-electrode configuration, namely working electrode, reference electrode and auxiliary electrode. In particular, the prototype shows a good agreement of CV in a standard electron transfer experiment by monitoring the interchange state of Fe2+ and Fe3+ ion in ferricyanide solution with potassium chloride supported, in comparison to that of the commercial potentiostat. Furthermore, the effects of different scan rate (0.05 to 0.15 V/s) and different ferricyanide concentrations from 1 to 7.5 millimolar are also evaluated to quantify sensing performance. Based on the obtained results, the calibration curve of anodic peak and cathodic peak current are linearly correlated with R2 of 0.9987 and 0.9990, respectively, providing a cost-effective (less than USD 80) and portable solution to the future integration of sensing technology.
Keywords: Biosensor; Electrochemical device; Wireless potentiostat